The Meidum Pyramid - Reader, Colin.
Located more than 70 km south of Cairo, the Meidum pyramid is noteworthy because of its square, tower-like shape and the difficulties associated with its attribution. Drawing from previously published material together with the author’s own observations from the site, the following paper will explore these two issues in order to reexamine the origins of this structure.